The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.09.26.509374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profound immunomodulatory effects of 225Ac-NM600 drive enhanced anti-tumor response in prostate cancer

Abstract: An immunosuppressive tumor microenvironment has hampered the efficacy of immunotherapy in prostate cancer. However, radiation-induced immunological effects can partly mediate anti-tumor effects by promoting a pro-inflammatory environment potentially responsive to immunotherapy. Herein, we examined the immunomodulatory properties of a radiopharmaceutical therapy (RPT) with NM600 radiolabeled with either a beta or alpha emitter in two prostate cancer models. 225Ac-NM600, but not 177Lu-NM600, promoted significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…They observed the highest decrease in CD8+ T cells at 19 days post-injection with 600 kBq/kg. However, no significant decrease in CD8+ T cells were observed in the Tramp-C1 TME after injection with 7.4 (∼300 kBq/kg) or 18.5 kBq (∼700 kBq/kg) of 225 Ac-NM600 (105). Moreover, 225 Ac-NM600 promoted a more active CD8+ T cell repertoire with increased expression of activation and proliferation markers such as CD44+, CD69+, and Ki67+ on CD8+ T cells, suggesting induction of an immunogenic TME by 225 Ac-NM600 which could be responsible for the antitumor response.…”
Section: Hematologicmentioning
confidence: 87%
See 2 more Smart Citations
“…They observed the highest decrease in CD8+ T cells at 19 days post-injection with 600 kBq/kg. However, no significant decrease in CD8+ T cells were observed in the Tramp-C1 TME after injection with 7.4 (∼300 kBq/kg) or 18.5 kBq (∼700 kBq/kg) of 225 Ac-NM600 (105). Moreover, 225 Ac-NM600 promoted a more active CD8+ T cell repertoire with increased expression of activation and proliferation markers such as CD44+, CD69+, and Ki67+ on CD8+ T cells, suggesting induction of an immunogenic TME by 225 Ac-NM600 which could be responsible for the antitumor response.…”
Section: Hematologicmentioning
confidence: 87%
“…Ferreira et al showed that 225 Ac-NM600 abrogated the infiltration of Treg cells in the TME of murine prostate cancer (105). In this study, they compared the anti-tumor and immune modulatory effect of 225 Ac-NM600 and 177 Lu-NM600 in two different immunocompetent prostate cancer models MyC-Cap in FVB/NJ mice or Tramp-C1 in C57BL/6 mice.…”
Section: Regulatory T (Treg) Cellsmentioning
confidence: 89%
See 1 more Smart Citation